Analisis Pengaturan dan Praktik Pemisahan Kekuasaan Sistem Pemerintahan Presidensial Berdasarkan Konstitusi - Zulfan, Zulfan (Media Hukum, 2018)
The founding fathers is agreed to embrace a presidential government system. The founding fathers is formulated the vision and mission of the Indonesian nation on the understanding of nationalism. This article would like to answer how the separation of powers in the presidential system based on the 1945 Constitution. The separation of powers arrangements and practices in the parliamentary system has already been applied in Indonesia. Post-independence, the relationship between the President and the House of Representatives in the implementation of the legislative function is not harmonious. Indonesia during the Old Orde was a phase of liberal democracy, then re-enacted Pancasila democracy. Based on its development, political instability helped determine the weaknesses in the implementation of separation of powers in Indonesia.